Field evaluation of phage fertilizer on controlling Ralstonia solanacearum in tomato and Erwinia mallotivora in papaya - Arif Radhi, Mohd Zafrul (2016)
The results of some previous studies have shown that bacteriophage, a virus that is 'eating' bacteria, by infecting and replicating in the bacterial cell-specific manner have potential to control plant pathogens. Bacterial wilt disease caused by Ralstonia solanacearum is one of the major threats to the cultivation of tomatoes in Malaysia. In addition, papaya dieback caused by Erwinia mallotivora also brings huge losses to the papaya growers across the country since 2005 until now. In this study, field evaluation was conducted to determine the effectiveness of phage fertilizer for controlling bacterial wilt disease in tomato and papaya dieback in papaya. This fertilizer plus bacteriophage is the one with specific crop nutrient requirements for both crops that has been incorporated with bacteriophage. The attempts on tomato plants showed T1 (ACI (All Cosmos Industries) fertilizer + bacteriophage) recorded the lowest score of 0.5 compared to T2 (ACI fertilizer only) of 1.56 and T3 (control) of 3.02. There were significant differences between T1 and T3 at p <0.05. Field study on papaya plants also recorded high percentage of plant mortality for all three treatments, T1, T2 and T3, three months after being inoculated with the pathogens E. mallotivora. T1 (ACI fertilizer + bacteriophage) recorded a percentage of 44.74% mortality, T2 (ACI fertilizer only) with 27.5% while T3 (control) with 69.77%. There was no significant difference between the three treatments recorded at p <0.05. This proves the specificity of bacteriophage to the host (bacterial pathogens) plays an important role in determining the success of disease control using phage.